Modeling the pre-metastatic niche of gastric cancer peritoneal metastasis under spatiotemporal resolution and investigating EVs-mediated immune suppression - Zhang, Xiang; Zhang, Cheng; Zhang, Zheng; Zhang, Xuan; Wang, Kai (Frontiers in Immunology, 2026)
Gastric cancer peritoneal metastasis (GCPM) is the leading cause of death in patients with advanced gastric cancer. The presence of ascites creates favorable conditions for the formation of the pre-metastatic niche (PMN), thereby providing a conducive environment for cancer cell metastasis. However, the mechanisms behind the formation of the pre-metastatic niche (PMN) are still not fully understood. This review examines the dynamic changes in the PMN of gastric cancer using organoid models combined with high spatiotemporal resolution and looks into the role of extracellular vesicles (EVs) in mediating immune suppression. It gives an overview of the latest advances in organoid modeling technologies, clarifies the biological characteristics of EVs, and discusses their functions in immune regulation. Furthermore, this review also highlights current challenges in this field, proposes future research directions, and identifies potential therapeutic targets. Bringing these insights together is intended to deepen understanding of gastric cancer metastasis and support the development of more effective therapeutic strategies.